Deployments, Combat Exposure, and Crime - D. Mark Anderson; Daniel I. Rees (Institute for the Study of Labor (IZA), 2013)
During the period 2001-2009, four combat brigades and the 3rd Armored Cavalry Regiment were based at Fort Carson, Colorado. These units were repeatedly deployed during the Iraq War, allowing us to measure the effect of arguably exogenous changes in troop levels on violent crime in El Paso County, where Fort Carson is located. Our results suggest that never-deployed units contributed to community violence in the form of assaults, murders, and robberies. In contrast, estimates of the relationship between the number of previously deployed units and violent crime are generally small and statistically insignificant. We conclude that soldiers returning from combat do not represent a special threat to public safety.
Keywords: K4; H56; 330; combat; crime; Iraq War; violence